Modern Approaches to Teaching in Medical Universities: Pendekatan Modern dalam Pengajaran di Universitas Kedokteran - Toyirovna, Yuldashova Shakhlo (Academia Open, 2025)
General Background: In modern medical education, traditional didactic methods are no longer sufficient to meet the dynamic demands of clinical practice. Specific Background: Uzbekistan’s medical universities are undergoing pedagogical reforms to emphasize creativity, integrative learning, and student-centered approaches. Knowledge Gap: Despite theoretical discourse on creative pedagogy, empirical frameworks integrating creativity into medical training in post-Soviet contexts remain underdeveloped. Aims: This study investigates how integrative-creative pedagogical methods influence the professional and cognitive development of medical students. Results: The findings reveal that integrating motivational, cognitive, and reflective components through clinical simulations and creative tasks enhances students’ independent thinking, problem-solving abilities, and professional identity. Novelty: The research codifies a model of integrative-creative pedagogy, highlighting student motivation, teacher improvisation, and reflective learning as essential components in fostering creative readiness. Implications: These insights contribute to educational reforms, suggesting that embedding creativity systematically into curricula cultivates more innovative, adaptable, and competent medical professionals ready to meet contemporary healthcare challenges. Highlight : Integrative-creative pedagogy boosts both professional and personal competencies in medical students. Motivation, reflection, and intuition are key components of creative readiness. The study proposes a model to systematically embed creativity into medical curricula. Keywords : Creative Thinking, Integrative Learning, Medical Education, Professional Readiness, Pedagogical